ON THE HISTORY OF PHILOSOPHY AS CRITERIA FOR EXPANDING SCIENTIFIC KNOWLEDGE - GHAZARYAN, ALBERT (Bulletin of Yerevan University E: Philosophy, Psychology, 2020)
Analyzing the corresponding works of E. Zeller, V. Chaloyan, H. Gabrielyan, the author of the article has set forth criteria for the history of philosophy, namely the acceptance and general recognition of scientific knowledge: The ideas of each author of the history of philosophy should be stated accurately, inconsistently, systematically, completely, wholly, as clearly as possible, definitely, elegantly, concisely, verifiably. The objectivity of the article should be preserved when drafting the material. The author’s party affiliation, national identity, personal sympathy should have the least influence on the content of the article. The authors and their ideas should be presented in the full socio-historical, cultural, paradigmatic, philosophical context of the given period. The content, particularities, similarities, and differences of the stated doctrine, as well as the borrowings and ideas from the teachings preceding it, should possibly fully and accurately be assessed by the doctrines that follow it. The historical impact of those ideas should be revealed and their subsequent transformation presented. The biographical data of the author, which have an impact on the perception of the ideas expressed in the article, should also be taken into account. If necessary, both external and internal criticism of the sources used should be made to ensure the accuracy of data and facts. Completeness of sources should possibly be ensured. Teachings that are historically stated must be classified with the utmost precision and accuracy.
Keywords: E. Zeller, V. Chaloyan, G. Gabrielyan, history of philosophy, validity of knowledge, objectivity, external criticism, internal criticism, completeness of sources